A Discourse Analysis of Interpersonal Metafunction in Vladimir Putin’s Speech Regarding Russia’s Invasion of Ukraine - M R Bustam (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
The present study discusses the strategies of discourse applied by Vladimir Putin in his speech regarding Russia's invasion of Ukraine. The goal of the study is to find out language strategies used by Vladimir Putin in his speech and the way he implements the realization of strategies in the speech. The method used in the study is qualitative descriptive method. In addition, when performing the analysis, the study uses Systemic Functional Grammar (SFG), especially the elements of interpersonal metafunction as the theoretical framework, to analyze the use of language in expressing social and personal relationships in the speech. The metafunction of interpersonal is often realized through the analysis of mood and modality. In the analysis of mood, it is possible to reveal the role that the speaker wants to be in the speaking situation, as well as the role that the speaker wants to assign to the listener. Moreover, in formal analysis, it cannot only show how the speaker perceives and thinks about the problem of the thesis topic, but also shows the power relationship and formal scale between the speaker and the listener. The results show that the design of Vladimir Putin's speech regarding Russia's invasion of Ukraine reflects his political intentions. All of this manifests not only in the speaking strategies of interpersonal metafunction he employs, but also in the interpersonal meanings he builds in the speech. In conclusion, it can be stated that the fact found in the study is completely understandable since Vladimir Putin is trying to convince the world that what he did in directing Russia's invasion of Ukraine was the correct decision, and that it did not jeopardize world peace.